COMPARATIVE ANALYSIS OF HUMILIATION OF MEN AND WOMEN IN RUSSIA AND THE USA - Suleymanov, Ramil; Fakhurdinova, Venera (Revista Inclusiones, 2020)
The research is devoted to the problem of estimating the manifestations of humiliation of men and women in Russia compared to the USA. The American sample included 253 respondents (170 women and 83 men) aged 15-51. The Russian sample consisted of 136 respondents (111 women and 25 men) aged 17-54. First, we adapted the technique “Test of the feeling of humiliation” (L. Hartling) to the Russian sample. The adapted technique showed the high validity and reliability of the test (p ≤ 0.05; p ≤ 0.01). It was shown that American women experience humiliation harder than men (impact of past humiliation p ≤ 0.05, fear of being humiliated p ≤ 0.01), while in the Russian sample the differences between men and women were not significant (p > 0.05). Comparison of the average scores of the Americans and the Russians (by mean scores) showed that the former experience humiliation harder than the latter. The results imply that the more favorable and stable social environment is, the more acutely various forms of humiliation are perceived, which was especially apparent in the American sample. At the same time, the Russians, living in more complicated conditions, get used to them and perceive humiliation less acutely